Mining Waste Potential Evaluation in the Ecological Blocks’ Production - Esnaider Rodríguez-Suárez; Manuel A. Valdir (Ciencia & Futuro)
This research project objective is to evaluate the potential of using abrasive sludge (RBRO) from the Huaxi Helin Mining Company in Manica province and fine coal refuse (RFC) from the ICVL Company in Tete province in the ecological blocks´production to the material discarded giving value after processing and it also helps to minimize the socioenvironmental impacts resulting from the waste accumulation. There were carried out bibliographical studies and samples, which were then subjected to laboratory tests using the granulometric analysis methods, X-ray fluorescence and X-ray diffraction at UEM. Comparative chemical characterizations were carried out on the standard specimens’ solid masses and those incorporated with RBRO and RFC percentages, and finally they were subjected to the compressive strength test (RC) at the LEM, in order to better assess their performance. It is shown that RBRO is basic in nature and has the following major elements: Si and Fe, with Calcite, Quartz, Anortite, Ilite and Magnesium niblende in the mineral range. The RFC falls into the fine aggregates’ rank and has the following major chemical elements: Fe, Si, S, Al, Ca, Ti and K, with kaolinite, quartz, palygorschist, muscovite, siderite and dolomite in the mineral range. The RC tests on the AM1 (6 %), AM3 (23 %) and AM4 (29 %) specimens showed satisfactory results, thus enabling them to meet the admissible resistance standards in Mozambique current standard. RBRO and RFC have the potential to be used in the ecological blocks´production.